(untitled) (Annals of Medical Research, 2021)
Aim: To assess the diagnostic accuracy of PI-RADS v2.1 using multi-parametric magnetic resonance imaging (mpMRI) to detect prostate cancer (pCa) and comparison with transrectal biopsy/radical prostatectomy results.Material and Methods: Between June 2017 and April 2019, 124 patients who underwent mpMRI prior to transrectal biopsy/ radical prostatectomy were evaluated by a pathology results-blinded uroradiologist using PI-RADS v2.1 categories, retrospectively. PIRADS v2.1 category results were compared with transrectal biopsy/radical prostatectomy results. All clinical data were used in statistical analysis.Results: The sensitivity, specificity, positive predictive value, negative predictive value and accuracy values of mpMRI using PI-RADS v2.1 categorization were 96%, 44%, 73%, 88% and 75%, respectively. A significant correlation was observed between a high PI-RADS score and high pathological grade (p0.001). The inter observer agreement expressed as the ICC was 0.65 (95% CI: 0.33–0.84, p 0.001).Conclusions: The mpMRI, used in conjunction with PI-RADS v2.1, is a useful and promising imaging method in detection of pCa. Keywords: Prostate cancer; multiparametric MRI; PI-RADS; transrectal biopsy; radical prostatectomy.